For how long should antibiotics be given in acute paediatric septic arthritis? A prospective audit of 96 cases. - Lavy, C; Thyoka, M (2007)
Ninety-six cases of uncomplicated acute septic arthritis in children aged 12 years and under were treated by arthrotomy under general anaesthesia, saline washout and antibiotics for six weeks. They were prospectively studied for 24 weeks to assess clinical, haematological and radiological changes. Clinical improvement was most marked in the first two weeks and did not change significantly after six weeks. Haematological indices (haemoglobin concentration, serum white cell count and erythrocyte sedimentation rate) all improved from the start of treatment and continued to improve throughout the study, even after antibiotics were finished. Radiological changes in the bone adjacent to the infected joint were noted to be present in 21 cases by two weeks after presentation, and in a further 10 cases by six weeks after presentation, suggesting some continued infective activity in the bone adjacent to the septic joint even after two weeks of antibiotics. No new radiological changes were noted after six weeks. It is therefore suggested that antibiotics in septic arthritis should be continued for six weeks.